Actuation, monitoring and closed-loop control of sewing machine presser foot - Silva, Luís F. (2003)
Sewing is one of the most important processes in the apparel industry for the production of high-quality garments. Although some research and improvements have been carried out in this area, the sewing process has remained almost unchanged throughout the years, staying largely dependent on the operator skills to set up sewing parameters and to handle the fabrics being sewn. Slight changes in sewing machine settings can influence the quality of seams, as well as sewing operation time. To avoid these empirical settings, reduce set-up times and improve machine performance, flexibility and sewing quality, an electromagnetic actuated presser foot, based on the use of a proportional force solenoid, was developed and implemented on an industrial overlock sewing machine. The compression force and displacement waveforms from the presser foot bar will be studied in this paper, as well as the admiss ible displacement limits used to monitor (on- and offline) fabrics’ feeding efficiency. Following this analysis, a new research programme was established to enable a PC-based open- and closed-loop control of the presser foot system. This paper also highlights these recent developments, presenting and discussing, in detail, a PID closed-loop control strategy. The obtained results show that the presser foot closed-loop control has improved performance for a wide speed variation range.